EUTHYROID SICK SYNDROME - Rai Purnami, Ni Ketu; Ratna Saraswati, Made; Sustika, I Ketut (journal of internal medicine, 2009)
Subclinical thyroid dysfunction is a common clinical problem for which there are many controversial issues regardingscreening, evaluation and management. Subclinical hypothyroidism is defined as an elevated serum TSH level associated withnormal total or free T4 and T3 levels. Euthyroid sick syndrome (ESS) identifies abnormalities in thyroid function tests observedin patients with systemic nonthyroidal illnesses (NTIs) and those undergoing surgery or fasting. Abnormalities of thyroid functionin NTIs have been classified as 1). Low T3 syndrome, 2). Low T3-low T4 syndrome, 3). High T4 syndrome, and 4). Otherabnormalities. The condition is not considered to need treatment because there are no symptoms and the tests go back to normalwhen the stressful illness has passed. It has been reported a case of euthyroid sick syndrome of a 49 years old woman, whoÕssuffering from sistemic illness of space occupaying lession in thoracal VII-VIII (with histopathologycal findings: metastaticadeno carcinoma). We found low levels of T3 (0.49 nmol/L) and TSH (<0.05 uI/ml), but normal levels of T4 (96.91nmol/L). Inseverely ill patients, T4 decreases and both T4 and T3 are inversely correlated with mortality rate.